Understanding the Barriers Limiting SMEs’ Capacity to Participate in Formal Training: A Perspective from an Emerging Market - Damoah, Obi Berko O.; Ashie, Augustina Adei; Elias, Kekesi Kodjo (PAN-AFRICAN JOURNAL OF BUSINESS MANAGEMENT, 2018)
Whilst SMEs are known to contribute significantly to the socio-economic development of most economies of the world, they are also known to face many challenges which limit their full effectiveness. The present study seeks to explore the factors that limit SMEs’ capacity to participate in formal training programmes from the Ghanaian perspective. The study seeks to identify the extent to which the barriers to training compare and contrast with existing studies, although the extant literature argues that some barriers are more specific to some regions. The study is based on a purposive sample of 85 owner-managed SMEs drawn from the capital of Ghana, Accra. Using the principal component analysis, coupled the mean rankings of the respondents’ average score as the main analytical tools, the results show that among the eight main barriers that were found, lack of accessibility to training, lack of funds to fund training programme and a negative perception of owner-managers regarding the usefulness of training were the three most important barriers accounting for why SMEs from Ghana find it difficult to participate in formal training and therefore remain inefficient and ineffective compared to their counterparts’ large firms.